Olfactory working memory: exploring the differences in n-back memory for high and low verbalisable odorants. Issue 10 (26th November 2019) - Moss, Andrew; Miles, Christopher; Elsley, Jane; Johnson, Andrew J.
ABSTRACT: We describe four experiments each examining n -back performance for high and low verbalisable odorants. Participants were presented with a sequence of odorants and were required to state if the current odorant was the same or different to the odorant presented two items earlier. Experiment 1 reported superior performance for high, relative to low, verbalisable odorants and was evident despite above-chance memory performance for the low verbalisable odorants. Experiment 2 showed that such superiority persisted with a concurrent articulation condition, suggesting that the memory benefit was not a consequence of verbal recording and rehearsal. Experiment 3 employed metacognitive judgments and showed that correct 2-back responses for high verbalisable odorants received more recollection responses compared to low verbalisable odorants. Experiment 4 compared n -back performance across different stimulus types and showed that, for high verbalisable odorants, performance correlated with both letters and abstract shapes, but such correlations were absent for low verbalisable odorants. Taken together, these findings show differences in n -back performance between high and low verbalisable odorants, and show that high verbalisable odorants exhibit performance similarities with both verbal and visual stimuli. We further argue that n -back performance for low verbalisable odorants operates differently to that of high verbalisable odorants.